Late-life Asian immigrants managing wellness through contributing to socially embedded networks - Wright-St Clair V; Nayar S; Kim H; Wang SM; Sodhi SK; Chung A; Suchdev J; Hu C (Taylor & Francis (Routledge))
New Zealand’s political, civic, health and social institutions have been criticised as being ill-prepared to serve the health and social needs of the country’s increasingly diverse ageing population. This grounded theory study examined how late-life Asian immigrants participate in community to influence their subjective health. Bilingual Chinese, Indian, and Korean local intermediaries and research assistants were engaged as collaborative research partners. Purposive recruitment, and later theoretical sampling, were used to identify the 24 Chinese, 27 Indian, and 25 Korean participants, aged 60-83, who were 1-19 years post-immigration. Data were gathered through nine focus groups, and 15 individual interviews in the participants’ language of choice. All data were recorded, transcribed verbatim, and translated to English for analysis. Data analysis was done using open coding, constant comparative analysis and dimensional analysis. Strengthening community was the core social process in the substantive theory developed. The participants actively advanced cultural connectedness and gave service with, and for, each other. Over time, they extended their focus toward doing so for the wider community. They purposely used long-standing, occupation-related skills to resource how they and their co-ethnic groups contributed to community health. Additionally, they sought novel opportunities to diversify their contributions. These late-life immigrants intentionally strove to stay healthy through doing. Achieving collective, as well as personal, health through community participation was for the sake of minimising potential burdens on the country’s health system. The results indicate good health promotion policies would aim to advance co-ethnic, socially embedded networks for late-life Asian immigrants.
Keywords: Asian health; Co-ethnic community; Community participation; Late-life immigrants; Subjective health; 1103 Clinical Sciences